The effect of genotype and storage on compositional, sensorial and textural attributes of canned fruit from commercially important non-melting peach cultivars - Christofi, Marina; Mauromoustakos, Andy; Mourtzinos, Ioannis T.; Lazaridou, Athina; Drogoudi, Pavlina D.; Theodoulidis, S.; Biliaderis, Costas G.; Manganaris, George A. (My University, 2021)
Peach (Prunus persica) fruit is widely consumed, both as fresh or as processed (mostly by canning) product. Despite its economic importance, a limited number of studies have dealt with quality assessment of clingstone peach cultivars after thermal processing. Thus, the aim of the current study was to evaluate the effect of canning process on compositional, sensorial and textural attributes of fruit from seven non-melting peach cultivars which exhibit on-tree ripening in succession, spanning from July till mid-September in the northern hemisphere. Descriptive quantitative analysis indicated discrete varietal differences, providing useful insights for the industry regarding the quality and marketing potential for canned products of each cultivar. Fruit packed in diluted-clarified grape juice concentrate, aiming towards a less caloric content product, demonstrated an inferior consumer perception regarding bitterness, astringency and off-taste. Storage of the canned fruit (6 versus 24 months) led to texture depletion modifications on a cultivar-dependent manner. ‘Ferlate®’ registered desirable textural properties, while ‘Mirel®’, besides the appealing orange-coloured fruit pieces, aligned with satisfactory sensorial properties, provide further marketing options for the peach canning industry. Both early (‘Romea’) and late-season ripening (‘VLG’) cultivars were proven amenable to canning with acceptable quality attributes, offering a sustainable solution towards extension of the non-melting peach harvesting season.
Keywords: Prunus persica; Clingstone; Texture; Sensory; Firmness; Fruit processing; Quantitative descriptive analysis